Testosterone-Induced Effects on Lipids and Inflammation - Stella Vodo; Nicoletta Bechi; Anna Petroni; Carolina Muscoli; Anna Maria Aloisi (Mediators of Inflammation)
Chronic pain has to be considered in all respects a debilitating disease and 10–20% of the world's adult population is affected by this disease. In the most general terms, pain is symptomatic of some form of dysfunction and (often) the resulting inflammatory processes in the body. In the study of pain, great attention has been paid to the possible involvement of gonadal hormones, especially in recent years. In particular, testosterone, the main androgen, is thought to play a beneficial, protective role in the body. Other important elements to be related to pain, inflammation, and hormones are lipids, heterogenic molecules whose altered metabolism is often accompanied by the release of interleukins, and lipid-derived proinflammatory mediators. Here we report data on interactions often not considered in chronic pain mechanisms.